Contribution of ALOS PALSAR DEM Imagery to the Study of Geological and Morphostructural Lineaments of Boma Trough Block, Onshore Coastal Basin of D.R. Congo - Shams Mbudi Diambu; Dominique Westhondo Osomba; Thomas Kanika Mayena; Clement N’zau Umba-di-Mbudi (MO.RI Publishing, 2023)
Geological and morphostructural lineaments are considered as the surface expression of geological structures and linear features of valleys, ridges and river drainage systems. Lineaments extracted from satellite images have always been effective in understanding the structural context of a region. The lineaments observed on the surface provide information on the tectonic stresses that have affected an area and give a first impression of the probable existence and orientation of geological structures that may constitute oil traps at depth. This study aims to semi-automatically extract lineaments (by combining the use of GIS software, remote sensing and operator intervention) in Boma Trough Block, an oil block located to the east of D.R. Congo Coastal Basin and still poorly explored. The satellite image used in this work is an ALOS PALSAR DEM with a spatial resolution of 12.5m, enhanced in traditional hillshade (solar azimuth of 315° and 45°) and multidirectional hillshade; which allowed the extraction of 3129 lineaments, with lengths ranging from 0.16 to 3.79 km, oriented on multidirectional hillshade at 47.1% along the NW-SE direction, at 44.1% along the NE-SW, 7.3% for N-S and 1.4% for E-W. Lineament density mapping revealed that areas with high and very high densities cover 43% of ??the study area, where the Precambrian basement is largely outcropping, while low and very low density areas represent 41% and contain sedimentary formations. Areas with moderate densities covered ??16%. The lineaments extracted from the DEM image compared to the reality on the field show a positive correlation. This confirms the important contribution of the processing approach used in this study.